MATHEMATICAL COMMUNICATION ABILITY AND LEARNING INTEREST (Experiment with Yunior High Student Using PQ4R Strategy) - Fatah, Jejen Abdul; Rohimat, Aang ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study is an experiment with pre test-post test control group design having a goal to analyze  the role of Preview, Question, Read, Reflect, Recite, Review (PQ4R) strategy on students’ mathematical communication  ability (MCA) and leraning interest (MLI). The study  involves 58 eighth grade students, a mathematical communication test, a mathematical  learning interest scale. The study found, on MCA, its N Gain, and on MLI, students getting treatment with PQ4R strategy attained better grades than the grades  of students taught by conventional teaching. The first group students attained at medium grade level on MCA and fairly good grade level on MLI, while the second group students  obtained  at low grade level on MCA, medium grade level on MLI, and they realized few difficulties in some  items of  mathematical communication tasks. The other findings, there was no association between MCA and MLI